Meeting the ambition of measuring the quality of hospitals' stroke care using routinely collected administrative data: a feasibility study. - Palmer, W; Bottle, A; Davie, C; Vincent, C; Aylin, P (2013)
OBJECTIVE: To examine the potential for using routinely collected administrative data to compare the quality and safety of stroke care at a hospital level, including evaluating any bias due to variations in coding practice. DESIGN: A retrospective cohort study of English hospitals' performance against six process and outcome indicators covering the acute care pathway. We used logistic regression to adjust the outcome measures for case mix. SETTING: Hospitals in England. PARTICIPANTS: Stroke patients (ICD-10 I60-I64) admitted to English National Health Service public acute hospitals between April 2009 and March 2010, accounting for 91 936 admissions. MAIN OUTCOME MEASURE: The quality and safety were measured using six indicators spanning the hospital care pathway, from timely access to brain scans to emergency readmissions following discharge after stroke. RESULTS: There were 182 occurrences of hospitals performing statistically differently from the national average at the 99.8% significance level across the six indicators. Differences in coding practice appeared to only partially explain the variation. CONCLUSIONS: Hospital administrative data provide a practical and achievable method for evaluating aspects of stroke care across the acute pathway. However, without improvements in coding and further validation, it is unclear whether the cause of the variation is the quality of care or the result of different local care pathways and data coding accuracy.